2020
DOI: 10.2147/ott.s236111
|View full text |Cite
|
Sign up to set email alerts
|

<p>EFEMP2 Suppresses the Invasion of Lung Cancer Cells by Inhibiting Epithelial-Mesenchymal Transition (EMT) and Down-Regulating MMPs</p>

Abstract: Background: Epidermal growth factor-containing fibulin-like extracellular matrix protein 2 (EFEMP2), also known as fibulin-4, MBP1 and UPH1, is an extracellular matrix protein associated with a variety of tumors. The purpose of this study was to investigate the prognostic value and the function of EFEMP2 in lung cancer. Methods: The mRNA and protein expression of EFEMP2 in lung normal and cancer tissues, lung cancer cell lines (A549, H460, H1299 and H1650) and normal epithelial cell line BEAS-2B were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…EFEMP2 is an extracellular matrix protein necessary for elastic fiber formation and connective tissue development, processes that are highly associated with tumor invasion and metastasis (42). The expression of EFEMP2 in bladder cancer tissues was significantly lower than that in normal tissues in previous study (43).…”
Section: Discussionmentioning
confidence: 85%
“…EFEMP2 is an extracellular matrix protein necessary for elastic fiber formation and connective tissue development, processes that are highly associated with tumor invasion and metastasis (42). The expression of EFEMP2 in bladder cancer tissues was significantly lower than that in normal tissues in previous study (43).…”
Section: Discussionmentioning
confidence: 85%
“…Many of these genes influence the capability of cells to migrate or to respond to mitogenic stimuli, are involved in extracellular matrix homeostasis [ 81 , 82 ] and can either promote or decrease EMT/mesenchymal characteristics depending on the cell type and disease state (cancerous as opposed to normal cells). For instance, TIMP3 and EFEMP2 suppress EMT in cancer cells and therefore tumour invasiveness through inhibition of metalloproteinase (MMP) genes ( Figure 5 C) [ 83 , 84 ], while elevation of TPM1/2 (encoding tropomyosins) in lens epithelial cells is associated with induction of EMT following injury through increased TGFβ (transforming growth factor) signalling [ 85 ], one of the main pathways to induce EMT [ 86 ]. Interestingly, in diabetic α-cells both EMT and TGFβ signalling marker genes are upregulated ( Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
“…Another report showed that DDR2 mediates stromal and cancer cell interaction in mesenchymal stem cells and metastasis growth in breast cancer (17,18). EFEMP2 significantly inhibits the invasion and metastasis of tumor cells and the process of epithelial-mesenchymal transition (EMT) through the Wnt/bcatenin pathway in lung, bladder, and breast cancers (19)(20)(21). Similarly, ITGBL1 is involved in tumor cell invasion and metastasis through the KRAS/EMT pathway (22).…”
Section: Discussionmentioning
confidence: 99%